Study on the effect of the dry extract Thang Thanh Giang Troc on blood pressure and urinary indices in a rat model of chronic kidney disease induced by five-sixths nephrectomies - Nguyen , Thi Dieu Linh; Le, Thi Thanh Nhan; Nguyen, Pham Ngoc Mai; Pham, Thuy Phuong (Tạp chí Y Dược cổ truyền Việt Nam, 2025)
pressure and urinary indices in a rat model of chronic kidney disease induced by five-sixths kidney resection. Subjects and methods: This study was conducted according to the method of Lu JR et al. (2014). Forty Wistar rats with CKD induced by 5/6 nephrectomy were divided into four groups: TTGT-1 and TTGT-2 (administered Thang Thanh Giang Troc extract at doses of 0.735 g/kg/day and 1.47 g/kg/day, respectively), the model group (given distilled water), and the reference group (treated with Enalapril at 10 mg/kg/day). In addition, a separate control group of 10 rats underwent sham operation without kidney removal and received distilled water. The intervention lasted 60 days, during which blood pressure and urine parameters were evaluated before and after treatment. Results: After 60 days of treatment, systolic, diastolic, and mean blood pressures, 24-hour urine volume, and proteinuria in the TTGT-1 and TTGT-2 groups were significantly reduced compared with pre-treatment levels and with those in the model group (p<0.01). Conclusion: The dry extract of Thang Thanh Giang Troc, administered at doses of 0.735 g/kg/day and 1.47 g/kg/day, produced statistically significant antihypertensive and renoprotective effects in the 5/6 nephrectomy rat model of chronic kidney disease (p<0.05). This experimental model offers a reliable foundation for future pharmacological and therapeutic research.